On sample size effects in fracture toughness determination of Bulk Metallic Glasses. (15th October 2018) - Geissler, D.; Freudenberger, J.; Wendrock, H.; Zimmermann, M.; Gebert, A.
Highlights: A critical and in-depth review of fracture toughness of Bulk Metallic Glasses (BMG). Effects of small specimen size for fracture toughness testing versus ASTM standards. At small specimen sizes overload failure instead of fracture from a critical crack. Geometric Test Condition Ratios for evaluation of size effects provided. Abstract: Bulk Metallic Glasses (BMG) show extraordinarily high values of strength and elastic strain. Despite the, in most cases, macroscopically brittle behaviour (especially in tension and bending), extremely high fracture toughness values are reported. Even though it is sometimes stated that huge plastic zones and strain softening make K -based approaches (ASTM E399) or J -integral based approaches (ASTM E1820) difficult for BMG, changes in material behaviour or intrinsic metallic glass materials properties are still inferred by many authors in order to explain the results. In addition, the limited dimensions of fully glassy bulk ingots mean that the available specimen sizes differ from those required by the common standards of fracture toughness testing. In this context, reported results from fracture toughness of prominent Pd-, Pt- and Zr-based BMG are analysed. An in-depth discussion of the size dependent effects on the mechanical loading conditions during fracture toughness testing is provided. As a result, it is shown that the differences and peculiarities of characterized BMG toughness mainly relate to geometrical/mechanical effects of small scale sample testing. They are not due to an intrinsic material property or to a size dependent ramification of intrinsic material behaviour.